The Political Process of Bureaucratic Reform: Wonosobo Regional Government Experience from 2011-2015 - I Made Krisnajaya; Suripto Suripto; Novi Paramita Dewi; Ambar Teguh Sulistiyani; Lutfi Untung Angga Laksana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2019)
This study examines the political process of bureaucratic reform in Wonosobo regional government from 2011-2015. The article uses political and bureaucratic frameworks to describe the interplay of bureaucrats and politicians in the phases of bureaucratic reform. Data collection for this study employed document review and in-depth interviews with key informants. Results of the study show that the political process of bureaucratic reform mainly involved dialectical interactions between actors in the Wonosobo Regional Government and the Regional House of Representatives. The interplay of actors can then be explained through the actors’ configuration, issues that are confronted by the actors, conflicts of interest between actors, and influence tactics used by actors in managing issues and struggling for their interests. The experience of the Wonosobo regional government shows that bureaucratic reform does not only concern technical and administrative capacities in carrying out institutional arrangement, but it also involves political aspects namely visionary leadership, strong political will to conduct reform, and effective use of influential tactics to gain political supports for the reform.